2020
DOI: 10.2147/cmar.s272652
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA PCAT18 Upregulates SPRR3 to Promote Colorectal Cancer Progression by Binding to miR-759</p>

Abstract: Background: Long noncoding RNAs (lncRNAs) play essential functions in the development of several cancers, including colorectal cancer (CRC). Nevertheless, how PCAT18 regulates CRC tumorigenesis remains unclear. In this research, we aimed to investigate the roles of PCAT18 in CRC. Materials and Methods: qRT-PCR and Western blot were used to analyze RNA and protein levels. CCK8, colony formation, transwell and wound healing assays were utilized to analyze proliferation, migration and invasion. Luciferase reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The luciferase activity was measured after 48 h transfection by using the Dual-Luciferase Reporter Assay (Promega, Shanghai, China). 30 , 31…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The luciferase activity was measured after 48 h transfection by using the Dual-Luciferase Reporter Assay (Promega, Shanghai, China). 30 , 31…”
Section: Methodsmentioning
confidence: 99%
“…The luciferase activity was measured after 48 h transfection by using the Dual-Luciferase Reporter Assay (Promega, Shanghai, China). 30,31 Statistical Analysis SPSS 18.0 software was used for statistical analysis. All experiments were repeated three times and the data were presented as the mean ± standard deviation (SD).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…The overexpression of HOPX , upregulation of p21, and downregulation of cyclin D1 and CDK4 regulate the progress of migration and invasion of MDA-MB-468 cells to modulate tumor growth of the breast [ 50 ]. Colorectal cancer (CRC) is an example where the expression of SPRR3 promotes the binding between PCAT18 and miR-759 and therefore restores a portion of the proliferation and invasion capabilities of CRC cells [ 51 ]. The combination of GO analysis and the literature review directly displays the connection between the proposed biomarker module and diverse cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PCAT18 promoted colorectal cancer cell proliferation, migration and invasion through binding miR-759 to promote the expression of SPRR. 13 The biological roles and mechanism of PCAT18 in human cancers are largely unknown. The current study aimed to investigate the exact roles and potential mechanism of PCAT18 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Nevertheless, Yang et al reported the oncogenic role of PCAT18 in colorectal cancer. 13 Obviously, the biological effects and underlying mechanism of PCAT18 in the development of main human cancers, including NSCLC, remain elusive.…”
Section: Introductionmentioning
confidence: 99%